Energy and environmental assessment and reuse of fluidised bed recycled carbon fibres - Meng, F.; McKechnie, Jon; Turner, T.A.; Pickering, S.J. (Elsevier, 2017)
Carbon fibre reinforced plastic (CFRP) recycling and the reutilisation of the recovered carbon fibre (rCF) 2 can compensate for the high impacts of virgin carbon fibre (vCF) production. In this paper, we evaluate the 3 energy and environmental impacts of CF recycling by a fluidised bed process and reuse to manufacture a 4 CFRP material. A ‘gate-to gate’ life cycle model of the CFRP recycling route using papermaking and 5 compression moulding methods is developed based on energy analysis of the fluidised bed recycling process 6 and processing of rCF. Key recycling plant operating parameters, including plant capacity, feed rate, and air 7 2 in-leakage are investigated. Life cycle impact assessments demonstrate the environmental benefits of recycled 8 CFRP against end of life treatments-landfilling, incineration. The use of rCF to displace vCF based on 9 material indices (equivalent stiffness and equivalent strength) therefore proves to be a competitive alternative 10 for composite manufacture in terms of environmental impact.